PENERAPAN PE.NDEKATAN INQUIRYDALAM PEMBELAJARAN SAINS SEBAGAI UPAYA PENGEMBANGAN CARA BERPIKIR DIVERGEN - Widowati, Asri (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Formal education until recently tend to teach students to fact memorizing and convergent thinking. It makes student have difficulties in solving problems that demand deep thinking and creative problem solving. Learning process in class tend to expect outcomes as knowledge, memory, and logic thinking. Students need to be motivated to think divergently. This is a serious issue since this kind of learning might results in reduction or even death of student's creativity. Developing creativity in science education, especially those that related to student's divergent thinking ability, require learning approaches that will encourage students to think well and able to give many alternative solutions to a single problem. Inquiry approach is the most effective one since this approach is student centered and persuades students to solve problem using scientific skills and researches. In other wordr, inquiry approach is a wcy in developing divergent thinking